Varicella-Related Hospitalizations Among Immunocompetent and Immunocompromised Children in Pre-Vaccine Era: A Tertiary Care Center Experience in Turkey - Özlem Akgün Doğan; Seda Topçu; Naciye Gönül Tanır (Galenos Yayinevi, 2018)
Aim: Although varicella is a common, contagious, self-limited childhood disease, it can cause significant long-term sequelae and mortality in both immunocompetent and immunocompromised children. The aim of the present study is to identify and review varicella-related hospitalizations, admissions and complications of primary varicella infection among immunocompetent and immunocompromised children of a large unselected local population in a governmental institution. Materials and Methods: Demographic aspects, clinical features, microbiological findings, complications, managements and outcome of the patients hospitalized for varicella were analyzed retrospectively. Results: Among 100 such children, 66 were immunocompetent and 34 were immunocompromised. Secondary bacterial infection was the most common complication in both groups. The second most common complication in the immunocompetent group was neurological complications (21%) followed by varicella-zoster virus (VZV) pneumonia (2%). In the immunocompromised group neurological complications and VZV pneumonia were not observed. Hematological complications were seen in 5% of the immunocompetent patients and 6% of the immunocompromised patients. Mortality was seen in 2% in the study group, one patient in the immunocompetent and one in the immunocompromised group. Conclusion: Despite a common perception of varicella infection being highly contagious but harmless, complications requiring hospitalization are frequent, potentially serious and costly even in healthy children. Since varicella virus vaccine prevents most of the morbidity and mortality caused by primary varicella in children, prevention rather than the treatment will be the optimal approach.